Kalibrasi Faktor Keamanan Global Pada Balok Beton Bertulang Eksisting - Hasyim, Wachid (Civil Engineering Department, Faculty of Engineering, Universitas Swadaya Gunung Jati, 2025)
In building construction, the safety and reliability of structural components ensure the overall safety of the building. The safety factor in building structures is demonstrated by the ability of a structure to withstand the loads acting upon it, where the building's safety factor can be measured using the concept of the global safety factor of the structure. This research aims to determine the magnitude of the safety factor and the design flexural resistance value of reinforced concrete beams according to the Global Safety Factor (GSF) concept. The resistance value obtained by calculating the global safety factor can serve as a reference in the design of beam structural components. The method used involves numerical analysis with a structural reliability analysis approach to obtain the resistance factor (γ) with the level of explanation in the research presentation being descriptive-numerical. Based on the analysis results, the global safety factor value obtained becomes a parameter influencing the design strength of the beam's resistance in terms of flexural strength. From the analysis results, the reliability index (β) was found to range between 7.80 and 8.30. Furthermore, the calculated safety factor (γR) was found to be in the range of 2.40 to 2.53. Additionally, the nominal resistance (Rm) and the global design resistance (Rd) of the beam were found to be 780.50 kNm and 325.21 kNm, respectively, indicating that the beam has been adequately designed to withstand bending moments under service conditions. Keywords: Global Safety Factor (γ), Global Design Resistance (Rd), Reliability Index (β).